A 2-bp deletion in intron 1 of TMEM182 is associated with TMEM182 mRNA expression and chicken body weight. Issue 1 (2nd January 2023) - Lin, Z. T.; Chen, G. H.; Peng, X.; Zhang, Z. H.; Li, T.; Lin, H. X.; Liang, S. S.; Zheng, Y. B.; Yao, Z. P.; Luo, W.
ABSTRACT: 1. Searching for molecular markers related to growth and carcase traits plays a critical role in improvement of the production performance of broilers. Previous studies found that transmembrane protein 182 (TMEM182) inhibits skeletal muscle development, growth, and regeneration, implying that the TMEM182 gene plays an important role during the development process of skeletal muscle. 2. A novel 2-bp indel in intron 1 of TMEM182 was detected in a yellow chicken population derived from the cross of White Recessive Rock chickens with Xinghua chickens, and three genotypes II (inserted homozygote), ID (inserted and deleted heterozygote) and DD (deleted homozygote) were observed. Association analyses indicated that the indel was significantly associated with the body weight, muscle fibre area, breast muscle weight and wing weight in the F2 population. 3. The expression of TMEM182 in leg muscle of chickens with II genotype was higher than that with DD genotype, with the 2-bp indel located in one of the putative PAX4 binding sites. Further research through luciferase assays revealed that the PAX4 could bind to the putative binding site and increase the TMEM182 transcription, with the 2-bp deletion disrupting the binding of PAX4. 4. The present study provides evidence for the association of the novel 2-bp indel in intron 1 of TMEM182 with the growth and carcase traits of chickens. This 2-bp indel could be used as a genetic marker in broiler breeding.